2012
DOI: 10.1161/atvbaha.111.236349
|View full text |Cite
|
Sign up to set email alerts
|

Aging Enhances the Basal Production of IL-6 and CCL2 in Vascular Smooth Muscle Cells

Abstract: Objective Increased circulating cytokine levels are a prominent feature of aging that may contribute to atherosclerosis. However, the role vascular cells play in chronic inflammation induced by aging is not clear. Here, we examined the role of aging on inflammatory responses of vascular cells. Methods and Results In an ex vivo culture system, we examined the inflammatory response of aortas from young (2-4 months) and aged (16-18 months) mice under non-stimulatory conditions. We found that basal levels of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
118
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(128 citation statements)
references
References 42 publications
5
118
1
1
Order By: Relevance
“…aneurysm), VR has been studied in various species including rats, rabbits, nonhuman primates, and humans, being an evolutionarily conserved process (see Table 3). The findings obtained have provided insights into the molecular and cellular mechanisms of aorta aging in humans [51][52][53][54][55][56][57][58][59][60]. Precisely, it has been shown that age-associated aorta VR is the result of a sterile inflammation, probably mediated by two supposed mechanisms: 1) infiltration of immune cells, that degrade tissues and release reactive or toxic molecules, causing DAMPs production [61]; 2) phenotypic changes in endothelial cells (ECs) and VSMCs evoked by altered and overload expression of stress and stretch signaling pathways, triggered by different stressors or damage tissue stimuli throughout life (i.e.…”
Section: Structural and Functional Features Of The Aorta In Physiologmentioning
confidence: 93%
See 2 more Smart Citations
“…aneurysm), VR has been studied in various species including rats, rabbits, nonhuman primates, and humans, being an evolutionarily conserved process (see Table 3). The findings obtained have provided insights into the molecular and cellular mechanisms of aorta aging in humans [51][52][53][54][55][56][57][58][59][60]. Precisely, it has been shown that age-associated aorta VR is the result of a sterile inflammation, probably mediated by two supposed mechanisms: 1) infiltration of immune cells, that degrade tissues and release reactive or toxic molecules, causing DAMPs production [61]; 2) phenotypic changes in endothelial cells (ECs) and VSMCs evoked by altered and overload expression of stress and stretch signaling pathways, triggered by different stressors or damage tissue stimuli throughout life (i.e.…”
Section: Structural and Functional Features Of The Aorta In Physiologmentioning
confidence: 93%
“…As a result of the long-term effects, they, in turn, determine vascular aging and the consequent cardiovascular dysfunction, responsabile of the development of several CVDs, such as sporadic TAA. [58] Vascular endothelial dysfunction and apoptosis during aging Monkeys Vascular endothelial dysfunction was present in oldmonkeys without evidence of atherosclerosis, which may be due to endothelial apoptosis and reduced endothelial cell density Wang M. et al [59] Proinflammatory signaling in age-associated arterial remodeling Rats A local proinflammatory signaling loop facilitates adverse age-associated arterial remodeling Song Y. et al [60] Expression inducing expression and/or activity of several pro-inflammatory transcription factors (located downstream to these pathways). Among these, first is the Nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) [41,61,71].…”
Section: Structural and Functional Features Of The Aorta In Physiologmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, recent experimental investigations in animal and ex vivo models report the role of TLR-4 pathway in the vascular aorta alterations (vascular remodeling -VR and medial degeneration-MD) and their complications, such as sporadic TAA. Precisely, they evidence as this pathway evocates or modulates increased expression and activation of endothelium dysfunction and extra matrix remodeling aorta pathways [56][57][58][59][60][61][62][63][64]. Pryshchep and colleagues demonstrated the TLR4-mediated signaling pathway expression in all cells of arterial wall and particularly in ECs and VSMCs.…”
Section: Tlr-4 Pathwaymentioning
confidence: 99%
“…Furthermore, Song and colleagues reported that signaling via TLR-4 pathway and its signal adaptors (i.e. MyD88) is responsible for the age-elevated basal IL-6 response using VSMCs from aged TLR-4-/-and Myd88-/-mice [59]. Eissler and colleagues observed an increased hypertension related to increased expression of TLR-4-mediated signaling pathway in vascular cells and consequent activation of ACE pathway in untreated hypertensive rats [56].…”
Section: Tlr-4 Pathwaymentioning
confidence: 99%